2023
DOI: 10.1038/s42005-023-01216-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal evolution of dense plasmas driven by intense x-ray fields

Abstract: The advent of x-ray free-electron lasers has enabled a range of new experimental investigations into the properties of matter driven to extreme conditions via intense x-ray-matter interactions. The femtosecond timescales of these interactions lead to the creation of transient high-energy-density plasmas, where both the electrons and the ions may be far from local thermodynamic equilibrium. Predictive modelling of such systems remains challenging because of the different timescales at which electrons and ions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This extensive ionization and collisional process lead to a Maxwellian distribution. Recent research has revealed that the effect of non-thermalized electron distribution 40) on both population and emission spectra becomes significant at laser intensities over ∼10 17 W cm −2 . Given that the laser intensity employed here is up to 10 12 W cm −2 or so, and is much smaller by 5 orders of magnitude, any potential contribution from non-thermal electrons is expected to be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…This extensive ionization and collisional process lead to a Maxwellian distribution. Recent research has revealed that the effect of non-thermalized electron distribution 40) on both population and emission spectra becomes significant at laser intensities over ∼10 17 W cm −2 . Given that the laser intensity employed here is up to 10 12 W cm −2 or so, and is much smaller by 5 orders of magnitude, any potential contribution from non-thermal electrons is expected to be negligible.…”
Section: Methodsmentioning
confidence: 99%